THE ROLE OF THE SCHOOL IN THE PROCESS OF SOCIALIZATION OF STUDENTS - Ashurova, Zulfiya (Журнал иностранных языков и лингвистики, 2021)
the article considers the aspect of school influence on the process of learner’s socialization. The au-thor reveals the problem of successful personal socialization, which a school should achieve by means of de-cent educational work. The article describes the possibility of successful influence on socialization by creating classroom mass-media.